Tie Dye Reborn : Sebagai Simponi Modern Warna-Warni dalam Konteks Pembelajaran di SD Negeri Desa Salakbrojo, Kedungwuni, Pekalongan - Ima Rosila; Umi Mahmudah (Dinamika Pembelajaran : Jurnal Pendidikan dan bahasa, 2025)
TIE DYE, a fabric dyeing technique that combines bright colors and unique patterns, which can be integrated into the context of art learning in elementary schools. At SDN Desa Salakbrojo, Kedungwuni, Pekalongan, the existence of the TIE DYE technique has begun to be introduced in the art education process, providing space for exploration of student creativity through a dynamic, colorful approach. This study aims to analyze the use of TIE DYE as an art learning method that can inspire students, improve fine motor skills, and introduce the concept of art in elementary education at SDN Desa Salakbrojo. This study uses a qualitative approach with a case study method. Data were collected through observation, interviews with teachers, and document analysis related to the implementation of the TIE DYE technique in learning. Data sources also include student work produced during the learning process. The results of this study indicate that TIE DYE can be used as an alternative learning method that is fun and effective in improving children's creativity and art skills. The use of this technique also provides new insights into how to integrate batik art into the elementary education curriculum, which can increase students' learning motivation and self-expression. Thus, TIE DYE can be part of the development of innovative art education in elementary schools. Keywords: tie dye reborn, jumputan batik, elementary school